(untitled) - Esch, Gerald W. (Cambridge, UK,New York, 2004)
Professor Gerald W. Esch, one of the world's leading ecological parasitologists, presents a series of essays on classic examples of field parasitology. The essays focus on the significance of the work and its contribution to the field but also on the people and, particularly, the sites at which the work took place. Taken together, they represent a beautifully written account of the development of an entire field of scientific endeavor spanning a period of 50 years or more. While the essays are not meant to be academic in a scientific sense, they contain a great deal of science. The book will be of great value to all parasitologists and ecologists, but also to anyone interested in how biological field work is carried out and how it contributes to greater understanding of the natural world
Keywords: Parasitology,Parasites,Sinh vật ký sinh